The value of 'binder-off' imaging to identify occult and unexpected pelvic ring injuries. Issue 2 (February 2018) - Fagg, James A.C.; Acharya, Mehool R.; Chesser, Tim J.S.; Ward, Anthony J.
Abstract: Aims: To determine the effectiveness of 'binder-off' plain pelvic radiographs in the assessment of pelvic ring injuries. Patients and methods: All patients requiring operative intervention at our tertiary referral pelvic unit/major trauma centre for high-energy pelvic injuries between April 2012 and December 2014 were retrospectively identified. Pre-operative pelvic imaging with and without pelvic binder was reviewed with respect to fracture pattern and pelvic stability. The frequency with which the imaging without pelvic binder changed the opinion of the pelvic stability and need for operative intervention, when compared with the computed tomography (CT) scans and anteroposterior (AP) radiographs with the binder on, was assessed. Results: Seventy-three percent (71 of 97) of patients had initial imaging with a pelvic binder in situ. Of these, 76% (54 of 71) went on to have 'binder-off' imaging. Seven percent (4 of 54) of patients had unexpected unstable pelvic ring injuries identified on 'binder-off' imaging that were not identified on CT imaging in binder. Conclusions: Trauma CT imaging of the pelvis with a pelvic binder in place is inadequate at excluding unstable pelvic ring injuries, and, based on the original findings in this paper, we recommend additional plain film 'binder-off' radiographs, when there is any clinical concern.